Strategic Management Of Public Relations In Islamic Education Institutions To Build Public Image And Increase Public Interest - Kejora, Sangga Cumbuan (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
This study aims to reveal the strategic management of public relations to build an image and increase public interest in An-Nur II Islamic Boarding School of Bululawang, Malang, with sub-focus covering: (1) concept of analysis and planning, (2) implementation process, and (3) evaluation process by PR management of An-Nur II Islamic Boarding School Bululawang, Malang. This study used a qualitative approach with a case study design. Data collection was done through in-depth interview techniques, participatory observation, and documentation. Data analysis techniques included data reduction, data presentation, and concluding. The validity of the findings carried out by extension of participation, source of triangulation techniques, theories, and methods, and perseverance of the observer. The research informants were boarding school caregivers, the person in charge of public relations, public relations of formal and non-formal educational institutions, work units / executive committee of public relations program, santri (students), parents, surrounding communities, and all relevant stakeholders. The results showed the facts obtained as evidence that An-Nur II Islamic Boarding School Bululawang Malang succeeded in building image and increasing public interest through strategic management of public relations, namely: 1) Award of The Best Islamic Boarding School, 2) Increasing new students interest every year, 3) Social empowerment and improvement of the community economy programs.